A Teaching English Through Literature-Based Instruction: A Holistic Approach to Language and Literary Skills - Iswahyudi, Sabrina Retnasari (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The connection between language learning and literary study has grown stronger over time (Novianti, 2016). Consequently, incorporating literature into classroom practices is encouraged as a way to blend both elements, offering more dynamic and meaningful educational experiences. Literature-based instruction has emerged as a valuable method in language education, making use of suitable literary texts to aid students in learning English. This study aims to explore how the integration of language and literature is applied in English teaching through literature-oriented techniques within an EFL learning environment. Conducted as a qualitative case study, the research took place at Junior High School located in Makassar, South Sulawesi, Indonesia. The data collection involved interviews, classroom observations, and document analysis. Following Miles and Huberman’s model, the data were processed through reduction, display, and conclusion. The findings demonstrate that literature-based instruction is highly relevant and should be further developed for teaching English to EFL learners. This instructional model supports various classroom activities that are in line with educational objectives, such as: (1) reading activities using literary works, (2) speaking practices inspired by literature, (3) listening exercises involving literary material, and (4) writing assignments based on literary themes. In essence, literature-based instruction validates that language and literature can be taught as a unified subject, fostering students’ growth in both linguistic and literary skills.